MODEL PEMBERDAYAAN EKONOMI ADAPTIF BERBASIS UNBOUNDED RATIONALITY DAN PERILAKU IRASIONAL: STUDI PADA WARGA BINAAN PEMASYARAKATAN DI RUTAN KELAS IIB SITUBONDO: (AN ADAPTIVE ECONOMIC EMPOWERMENT MODEL BASED ON UNBOUNDED RATIONALITY AND IRRATIONAL BEHAVIOR: A STUDY OF COMMUNITY INMATES IN CLASS IIB SITUBONDO PRISON) - Kristiawan, Rudi; Zainuri, Zainuri; Wilantari, Regina Niken; Saleh, Mohammad (e-Journal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to examine the effectiveness of skill-based economic empowerment programs at Class IIB Detention Center Situbondo and to formulate an adaptive economic empowerment model grounded in behavioral economics. The findings reveal that the economic behavior of inmates does not align with the classical assumption of unbounded rationality. Instead, decisions are driven by fear of failure, social pressure, and past trauma, which manifest as cognitive biases such as loss aversion and status quo bias. The avoidance of economically beneficial training opportunities reflects a form of contextual and defensive rationality, wherein individuals prioritize avoiding loss over pursuing uncertain gains. A satisficing strategy, offering simple and achievable options, proved more effective than utility-maximization approaches. Institutional support, humanistic approaches by officers, and incentive systems based on progress significantly enhance program engagement. This study presents a model that aligns with bounded rationality and psychosocial realities, contributing theoretically by framing irrational behavior as an adaptive response to high structural risk.